Degradation of hyaluronic acid derived from tilapia eyeballs by a combinatorial method of microwave, hydrogen peroxide, and ascorbic acid. (February 2015) - Chen, Shengjun; Chen, Hui; Gao, Ruichang; Li, Laihao; Yang, Xianqing; Wu, Yanyan; Hu, Xiao
Abstract: Hyaluronic acid (HA) derived from tilapia eyeballs was depolymerized by microwave irradiation with ascorbic acid and hydrogen peroxide. Its effects on the structure of hyaluronic acid were determined by ultraviolet spectra (UV) and Fourier transform infrared spectra (FTIR). Molecular weight and the content of glucuronic acid were used as the index for comparison of the different effects of microwave alone, hydrogen peroxide combined with ascorbic acid, and microwave combined with ascorbic acid and hydrogen peroxide. The results showed that HA can be effectively degraded by a combinatorial method of microwave, hydrogen peroxide, and ascorbic acid. The optimal degradation condition was a 1:1 mol ratio between hydrogen peroxide and ascorbic acid at pH 4.0 at 30 min of reaction time and 60 °C of reaction temperature. The low molecular weight oligomeric product of HA was obtained, and the molecular weight of HA was <5 kDa. The content of glucuronic acid in degraded HA was 34.96%, and the yield of the degraded HA was 77.43%. The overall spectral pattern of FTIR and UV did not change between HA and low molecular weight HA (LMW-HA) degraded by the combinatorial method, demonstrating only minor damage to the structure of HA during the degradation process.